2022
DOI: 10.1145/3478520
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Dynamic Binary Instrumentation Systems for Conspicuous Features and Artifacts

Abstract: Dynamic binary instrumentation (DBI) systems are a popular solution for prototyping heterogeneous program analyses and monitoring tools. Several works from academic and practitioner venues have questioned the transparency of DBI systems, with anti-analysis detection sequences being found already in malware and executable protectors. The present Field Note details new and established detection methods and evaluates recent versions of popular DBI systems against them. It also sets out reflections on potential re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…9. The instrumentation mechanism of drltrace passes Test T2 for all but a few APIs: the test incidentally reveals artifacts of DynamoRIO, which alters several kernel32.dll APIs for its working [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9. The instrumentation mechanism of drltrace passes Test T2 for all but a few APIs: the test incidentally reveals artifacts of DynamoRIO, which alters several kernel32.dll APIs for its working [34].…”
Section: Discussionmentioning
confidence: 99%
“…The design of SNIPER does not address evasions targeting the peculiarities of the underlying instrumentation technique. For this well-studied problem [34], [40], [41], the implementation can resort to existing mitigations, such as patching the Time Stamp Counter in the VM monitor upon VM exit events or hiding artifacts of a DBI runtime as we did by using the mitigation library of [11].…”
Section: Residual Attack Surfacementioning
confidence: 99%
“…We gather the instructions and memory traces utilizing IntelPIN [33,16] (step 4 in the figure). To only collect the traces of the WebAssembly execution with a wasmtime engine, we pause and resume the collection as the execution leaves and re-enters the WebAssembly code, respectively.…”
Section: Protocol For Rq2mentioning
confidence: 99%
“…At the same time, we have covered a variety of code-transformation approaches. Setting Android-based obfuscation tools involves more than selecting features [56,57]. In addition, many complicated circumstances make obfuscating specific parts of code complex or impossible to understand, and even if that code is obscured, the app will no longer operate.…”
Section: Android Security Vulnerabilities and Existing Obfuscation Te...mentioning
confidence: 99%
“…Dietzel et al [243] offered a false responder agent that provides misleading values to the malware regarding the execution environment. Singh [179] used the detection of user interactions and anti-emulators to enhance the resilience of identifying dynamic malware [244]. Petsas et al [115] suggested several countermeasures for different types of evasion detection, such as anti-emulation employing IMEI alteration and precise sensor simulation.…”
Section: (A)mentioning
confidence: 99%